Governing cross-sector collaboration - Forrer, John J. (Jossey-Bass nonprofit sector series., 2014)
"A comprehensive guide to public sector collaboration with private and nonprofit organizations for better service deliveryGoverning Cross-Sector Collaboration tackles the issues inherent in partnerships with nongovernmental actors for public service delivery, highlighting the choices available and the accompanying challenges and opportunities that arise. Based on research, interviews with public, private and nonprofit sector leaders, and considerable analysis of organizations involved in public-private-nonprofit collaborations, the book provides insight into cross-sector collaboration at the global, federal, state, and local levels. Through an examination of the primary modes of cross-sector collaboration, including collaborative contracting, partnerships, networks, and independent public services providers, the book presents a clear case for how public managers can assess the trade-offs and use these options to improve public service delivery. Nonprofit organizations, businesses, and third-party contractors are increasingly partnering with government to deliver public services. Recognizing the types of collaborative approaches, and their potential to solve public policy problems is quickly becoming a major task for public managers, with new methods and techniques constantly emerging. Governing Cross-Sector Collaboration provides specific examples and a framework for public managers to make strategic choices about how to engage private and nonprofit actors in delivering public goods and services while ensuring the public interest. The book provides effective methods for choosing, designing, governing, and evaluating networks, partnerships, and independent public-services providers, with in-depth discussion encompassing: Analysis and engagement of cross-sector organizations Fostering democratic accountability in the public interest Collaborative approaches (including contracts, networks and partnerships) and the issues associated with each type of arrangement Leadership and organizational learning in cross-sector collaboration Included case studies illustrate effective application of the concepts and methods described, providing both practicing public and nonprofit managers and public policy/administration students with insight into these emerging strategic alliances. The first comprehensive guide to public governance collaborations, Governing Cross-Sector Collaboration is an important and timely contribution to the field of public management"--